Robert J. Patten (1944–2017): Life, Legacy, and Contributions to Archaeology, Lithic Technology, and Flintknapping. (3rd July 2019) - Eren, Metin I.; Patten, Lauren E.
ABSTRACT: Robert J. Patten passed away suddenly on February 8, 2017. His influence on flintknapping, lithic technology, and archaeology, however, continues on. Here, we review Patten's life and myriad contributions.